2018
DOI: 10.3233/jnd-180320
|View full text |Cite
|
Sign up to set email alerts
|

Mastication and Oral Motor Function in McArdle Disease: Patient Reported Complaints

Abstract: In short, reported mastication difficulties are prevalent in people with McArdle disease, most frequently in younger people. Therefore, awareness of mastication and oral motor problems is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Oral function evaluation may help confirm the effectiveness of treatment, and predict future general-health deterioration [ 8 ]. It is also known that decreased oral function is a prodromal symptom of severe diseases including neuromuscular conditions [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. It is clearly important to conduct oral function examinations on a broad range of patients, since they have the potential to incidentally detect severe diseases at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Oral function evaluation may help confirm the effectiveness of treatment, and predict future general-health deterioration [ 8 ]. It is also known that decreased oral function is a prodromal symptom of severe diseases including neuromuscular conditions [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. It is clearly important to conduct oral function examinations on a broad range of patients, since they have the potential to incidentally detect severe diseases at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations in patients with GSD V are comparable to those with GSD II. GSD V also affects the muscles, and this is due to the deficiency of muscular phosphorylase [43]. Patients show a muscular intolerance syndrome to the effort, associated with myalgia, cramps, fatigue and muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Only two articles included in our study showed the presence of oral manifestations in patients with GSD V. Both articles reported painful symptoms, such as the presence of cramps, and therefore masticatory difficulty in these patients [42,43].…”
Section: Gsd Vmentioning
confidence: 99%
“…There is often observed a decrease in symptoms after a brief period of rest, and this phenomenon is called "second wind", characterized by a partial recovery due to the decrease in cardiac frequency during the rest period, allowing the individual to recover and tolerate exercise for a longer period of time [9]. Recently, it has also been observed that younger individuals with McArdle's disease often present problems with mastication and oral motor function skills [10].…”
Section: Discussionmentioning
confidence: 99%